Non-aqueous electrolyte storage element and method for producing the same

By using phosphorus-containing positive electrode composite and moderate concentration of imide salt in the nonaqueous electrolyte power storage element, the problem of rising internal resistance after charging and discharging is solved, and the capacity retention rate and low-temperature performance are improved.

CN111316494BActive Publication Date: 2025-04-25GS YUASA INT LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN201880067518.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2017-10-20
Filing Date
2018-09-14
Publication Date
2025-04-25
Estimated Expiration
2038-09-14

AI Technical Summary

Technical Problem

When using imide salt as the electrolyte salt, the internal resistance of the nonaqueous electrolyte power storage element increases significantly after the charge and discharge cycle, and the high-rate discharge performance at low temperatures is reduced.

Method used

A positive electrode composite material containing phosphorus atoms was used, and a moderate concentration of imide salt was used in the non-aqueous electrolyte to ensure that the P2p peak exists at a position below 135 eV in the X-ray photoelectron spectrum of the positive electrode composite material.

Benefits of technology

It effectively suppresses oxidative corrosion of aluminum, prevents the rise of internal resistance, and improves the capacity retention rate after charging and discharging cycles, improving the high-rate discharge performance at low temperatures.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN111316494B_ABST
    Figure CN111316494B_ABST
Patent Text Reader

Abstract

One embodiment of the present invention is a non-aqueous electrolyte storage element, comprising: a positive electrode having a positive electrode composite material containing phosphorus atoms, and a non-aqueous electrolyte containing an imide salt, wherein in the X-ray photoelectron spectrum of the positive electrode composite material, a peak attributable to P2p exists at a position below 135 eV. Another embodiment of the present invention is a method for manufacturing a non-aqueous electrolyte storage element, using a positive electrode and a non-aqueous electrolyte containing an imide salt, wherein the positive electrode has a positive electrode composite material made using a positive electrode composite material paste containing an oxygen-containing acid containing phosphorus.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a nonaqueous electrolyte electricity storage element and a method for producing the nonaqueous electrolyte electricity storage element. Background Art

[0002] Non-aqueous electrolyte secondary batteries represented by lithium ion secondary batteries are widely used in electronic devices such as personal computers, communication terminals, and automobiles due to their high energy density. The above-mentioned non-aqueous electrolyte secondary batteries generally have a pair of electrodes electrically isolated by a separator and a non-aqueous electrolyte between the electrodes, and are composed of a charging and discharging mode by performing ion transfer between the two electrodes. In addition, as non-aqueous electrolyte storage elements other than non-aqueous electrolyte secondary batteries, capacitors such as lithium ion capacitors and double electric layer capacitors are also widely popular.

[0003] As one type of electrolyte salt used for non-aqueous electrolytes, imide salts such as lithium bis(fluorosulfonyl)imide (LiFSI) are known. Compared with LiPF6 and other widely used electrolyte salts, imide salts have a higher dissociation between cations and anions. Therefore, non-aqueous electrolyte storage elements using imide salts can expect good high-rate discharge performance at low temperatures. However, it is known that when imide salts are used as electrolyte salts, the working potential of the positive electrode is 4.0V (vs. Li / Li + ) or more, which causes oxidative corrosion of aluminum used as a positive electrode substrate of a non-aqueous electrolyte storage element, and reduces the charge and discharge performance. In contrast, it has been reported that the working potential of the positive electrode can be suppressed to 4.0 V (vs. Li / Li) by using an imide salt at a high concentration. + ) or more during charge and discharge (see Patent Document 1, Abstract of Non-Patent Document 1). Regarding the specific concentration of imide salt that can achieve this inhibitory effect, for example, paragraph

[0012] of Patent Document 1 states that "when the voltage is 4.5V, no corrosion is observed when the LiFSI is 1.5mol / L or more, and when the voltage is as high as 4.9V, no corrosion is observed if the LiFSI is 4mol / L".

[0004] Prior art literature

[0005] Patent Literature

[0006] Patent Document 1: Japanese Patent Application Publication No. 2015-79636

[0007] Non-patent literature

[0008] Non-patent literature 1: Jianhui Wang et al., “Superconcentrated electrolytes for a high-voltage lithium-ion battery”, Nature Communications, 2016, 7: 12032 doi: 10.1038 / ncomms12032 Summary of the invention

[0009] In non-aqueous electrolyte storage elements, as described above, when imide salts such as LiN(SO2F)2(LiFSI), LiN(C2F5SO2)2(LiBETI), and LiN(CF3SO2)2(LiTFSI) are used as electrolyte salts at a general concentration of about 1 mol / kg, the positive electrode is 4.0V (vs. Li / Li + ) or more, oxidative corrosion of aluminum is likely to occur. When oxidative corrosion of aluminum occurs, the internal resistance greatly increases with the charge and discharge cycle, so it is not preferred. On the one hand, by using a non-aqueous electrolyte containing a high concentration of imide salts, oxidative corrosion of aluminum can be suppressed, but in this case, the viscosity of the non-aqueous electrolyte increases and the internal resistance also increases. The increase in the viscosity of the non-aqueous electrolyte will reduce the good high-rate discharge performance at low temperature of the non-aqueous electrolyte storage element using imide salts, which is one of the advantages of using imide salts, and is therefore not preferred.

[0010] The present invention has been made in view of the above situation, and its purpose is to provide a non-aqueous electrolyte storage element and a method for manufacturing such a non-aqueous electrolyte storage element that solves the problem that the internal resistance after charge and discharge cycles increases significantly when an imide salt is used as an electrolyte salt in a concentration range that is not high.

[0011] One embodiment of the present invention completed to solve the above-mentioned problems is a non-aqueous electrolyte storage element, comprising: a positive electrode having a positive electrode composite containing phosphorus atoms, and a non-aqueous electrolyte containing an imide salt; in the X-ray photoelectron spectrum of the above-mentioned positive electrode composite, a peak belonging to P2p exists at a position below 135 eV.

[0012] Another embodiment of the present invention is a method for producing a nonaqueous electrolyte storage element, using a positive electrode having a positive electrode composite material produced using a positive electrode composite material paste containing an oxoacid containing phosphorus, and a nonaqueous electrolyte containing an imide salt.

[0013] According to the present invention, a nonaqueous electrolyte storage element and a method for producing such a nonaqueous electrolyte storage element can be provided that solves the problem that the internal resistance after charge and discharge cycles increases significantly when an imide salt is used as an electrolyte salt within a concentration range that is not high. BRIEF DESCRIPTION OF THE DRAWINGS

[0014] Figure 1 This is a perspective view showing the appearance of a non-aqueous electrolyte storage device according to one embodiment of the present invention.

[0015] Figure 2 This is a schematic diagram showing a power storage device constituted by assembling a plurality of nonaqueous electrolyte power storage elements according to one embodiment of the present invention. DETAILED DESCRIPTION

[0016] A nonaqueous electrolyte storage element according to one embodiment of the present invention comprises a positive electrode having a positive electrode composite material containing phosphorus atoms, and a nonaqueous electrolyte containing an imide salt, wherein in the X-ray photoelectron spectrum of the positive electrode composite material, a peak attributable to P2p exists at a position below 135 eV.

[0017] According to the non-aqueous electrolyte storage element, even if the imide salt in the non-aqueous electrolyte is not made to be a high concentration, the oxidative corrosion of aluminum can be suppressed, and the rise of the internal resistance after the charge and discharge cycle can be suppressed. The reason for the above-mentioned effect in the non-aqueous electrolyte storage element is not clear, but it is speculated to be the following reasons. When the positive electrode composite material is formed by the positive electrode composite paste containing the oxygen-containing acid of phosphorus, a film containing the following components is formed, and the components come from the oxygen-containing acid of phosphorus, and the peak belonging to P2p in the X-ray photoelectron energy spectrum exists at a position below 135eV. It is speculated that since the film suppresses the oxidative corrosion of aluminum as a positive electrode substrate, the internal resistance does not increase, and the rise of the internal resistance after the charge and discharge cycle is suppressed. It should be explained that the reason is still uncertain, but the effect of suppressing the rise of the internal resistance after the charge and discharge cycle is a specific effect produced only when using an imide salt as an electrolyte salt and using a positive electrode composite material with a peak belonging to P2p in the X-ray photoelectron energy spectrum at a position below 135eV. In addition, according to the nonaqueous electrolyte storage element, the capacity retention rate after the charge-discharge cycle can also be improved. The reason why the capacity retention rate improves is also unclear, but it is speculated that it is also due to the film containing the composition of the position below 135eV that the peak belonging to P2p in the X-ray photoelectron spectrum suppresses the oxidative corrosion of aluminum. In addition, according to the nonaqueous electrolyte storage element, as mentioned above, even if the imide salt is not made to be high concentration, the rise of the internal resistance after the charge-discharge cycle can be suppressed. Therefore, the nonaqueous electrolyte storage element can improve the undesirable aspects of the nonaqueous electrolyte storage element using the imide salt of high concentration such as the high viscosity and internal resistance in the past, even if the imide salt is designed to be not a high concentration concentration range, it can also be preferably used.

[0018] It should be noted that the sample (positive electrode composite material) used in the measurement of X-ray photoelectron spectroscopy is prepared by the following method. The non-aqueous electrolyte storage element is discharged at a current of 0.1C to the discharge end voltage during normal use to reach a fully discharged state. The storage element in the fully discharged state is disassembled and the positive electrode is taken out. The positive electrode is thoroughly cleaned with dimethyl carbonate and then dried under reduced pressure at room temperature. The dried positive electrode is cut into a predetermined size (for example, 2×2 cm) and used as a sample for the measurement of X-ray photoelectron spectroscopy. The operation from the disassembly of the non-aqueous electrolyte storage element to the preparation of the sample for the measurement of X-ray photoelectron spectroscopy is carried out in an argon atmosphere with a dew point of less than -60°C. The prepared sample is sealed in a transfer vessel and maintained in an argon atmosphere with a dew point of less than -60°C, and introduced into the sample chamber of the measurement device of X-ray photoelectron spectroscopy. The device used in the measurement of X-ray photoelectron spectroscopy and the measurement conditions are as follows.

[0019] Installation: "AXIS NOVA" by Kratos Analysis

[0020] X-ray source: monochromatized AlKα

[0021] Accelerating voltage: 15 kV

[0022] Analysis area: 700μm×300μm

[0023] Measurement range: P2p = 145 ~ 128eV, C1s = 300 ~ 272eV

[0024] Measurement interval: 0.1eV

[0025] Measurement time: P2p = 72.3 seconds / time, C1s = 70.0 seconds / time

[0026] Cumulative times: P2p = 15 times, C1s = 8 times

[0027] In addition, the position of the peak in the above energy spectrum is the value obtained as follows. First, the position of the peak of C1s belonging to sp2 carbon is set to 284.8 eV, and the binding energy of the entire energy spectrum obtained is corrected. Next, the corrected energy spectrum is horizontalized by removing the background using the straight line method. In the energy spectrum after the horizontalization process, the peak belonging to P2p is taken as the position of the peak belonging to P2p, which has the highest binding energy.

[0028] In the non-aqueous electrolyte storage element, the content of the above-mentioned imide salt in the above-mentioned non-aqueous electrolyte is preferably 0.5mol / kg to 2mol / kg. According to the non-aqueous electrolyte storage element, even if the imide salt is used in a concentration range that is not such a high concentration, the oxidative corrosion of aluminum can be suppressed. Therefore, in the non-aqueous electrolyte storage element, it is not necessary to use the imide salt at a high concentration. In addition, usually, when the imide salt is used at a high concentration, the viscosity increases and the internal resistance increases. In contrast, by making the concentration of the imide salt in the non-aqueous electrolyte in the non-aqueous electrolyte storage element in a concentration range that is not as high as the above range, the internal resistance can be kept from increasing, and the increase in the internal resistance after the charge and discharge cycle can be suppressed. In addition, since the viscosity of the non-aqueous electrolyte containing the imide salt in a concentration range that is not such a high concentration is small, it can be expected to improve the high-rate discharge performance at low temperatures, etc.

[0029] In the nonaqueous electrolyte storage element, the maximum potential of the positive electrode is preferably 4.4 V (vs. Li / Li + ) or more, more preferably 4.5V (vs.Li / Li + ) or more, more preferably 4.6V (vs.Li / Li + According to this non-aqueous electrolyte storage element, even when using an imide salt, the maximum potential of the positive electrode is 4.4 V (vs. Li / Li + ) or more, the internal resistance after the charge and discharge cycle can also be reduced. Therefore, by making the maximum potential of the positive electrode 4.4V (vs. Li / Li + ) or more, the internal resistance after the charge and discharge cycle can be suppressed, and the positive electrode can be kept at 4.4V (vs. Li / Li + ) or higher operating potential for charge and discharge.

[0030] A method for producing a nonaqueous electrolyte storage element according to one embodiment of the present invention is a method for producing a nonaqueous electrolyte storage element using a positive electrode having a positive electrode composite material produced using a positive electrode composite material paste containing an oxyacid of phosphorus and a nonaqueous electrolyte containing an imide salt.

[0031] By using a positive electrode composite paste containing an oxygen-containing acid of phosphorus, a positive electrode composite material having a peak attributable to P2p in an X-ray photoelectron spectrum at a position below 135 eV is obtained. Therefore, according to this manufacturing method, a non-aqueous electrolyte storage element can be manufactured that can suppress the increase in internal resistance after charge and discharge cycles even when an imide salt is used in a concentration range that is not a high concentration.

[0032] Hereinafter, a nonaqueous electrolyte electricity storage element and a method for producing the nonaqueous electrolyte electricity storage element according to an embodiment of the present invention will be described in detail.

[0033] <Non-aqueous electrolyte energy storage device>

[0034] The nonaqueous electrolyte storage element of one embodiment of the present invention has a positive electrode, a negative electrode and a nonaqueous electrolyte. Below, as an example of a nonaqueous electrolyte storage element, a nonaqueous electrolyte secondary battery is described. The positive electrode and the negative electrode are usually stacked or wound across a separator to form an electrode body that overlaps alternately. The electrode body is housed in a container and filled with the nonaqueous electrolyte in the container. The nonaqueous electrolyte is between the positive electrode and the negative electrode. In addition, as the above-mentioned container, a known metal container, a resin container, etc. commonly used as a container of a nonaqueous electrolyte secondary battery can be used.

[0035] (positive electrode)

[0036] The positive electrode comprises a positive electrode substrate and a positive electrode mixed material layer disposed on the positive electrode substrate directly or via an intermediate layer.

[0037] The positive electrode substrate has electrical conductivity. As the material of the substrate, metals such as aluminum, titanium, tantalum, stainless steel, or their alloys can be used. Among them, aluminum and aluminum alloys are preferred from the perspective of balancing high electrical conductivity and cost. In addition, when the positive electrode substrate is aluminum or an aluminum alloy, it is possible to more fully exert the effect of suppressing the increase in internal resistance after charge and discharge cycles of the non-aqueous electrolyte storage element, which is presumed to be mainly caused by oxidative corrosion of aluminum. As the formation form of the positive electrode substrate, foil, vapor-deposited film, etc. can be cited. From the perspective of cost, foil is preferred. In other words, as the positive electrode substrate, aluminum foil is preferred. It should be noted that as aluminum or aluminum alloy, A1085P, A3003P, etc. specified in JIS-H-4000 (2014) can be exemplified.

[0038] The intermediate layer is a coating layer on the surface of the positive electrode substrate, and contains conductive particles such as carbon particles to reduce the contact resistance between the positive electrode substrate and the positive electrode composite layer. The composition of the intermediate layer is not particularly limited, and for example, it can be formed from a composition containing a resin binder and conductive particles. It should be noted that "conductive" means that the volume resistivity measured in accordance with JIS-H-0505 (1975) is 10 7 Ω·cm or less, "non-conductive" means that the volume resistivity is more than 10 7 Ω·cm.

[0039] The positive electrode composite material layer is a layer formed by a positive electrode composite material. The positive electrode composite material contains a positive electrode active material and phosphorus atoms, and further contains other conductive agents, binders, thickeners, fillers, dispersants and other arbitrary components as needed. In the X-ray photoelectron spectrum of the positive electrode composite material, the peak attributed to P2p exists at a position below 135eV. The positive electrode composite material layer is usually formed on the surface of the positive electrode substrate by coating and drying a positive electrode composite material paste containing a positive electrode active material and an oxygen-containing acid of phosphorus. Among them, in the non-aqueous electrolyte storage element, part or all of the oxygen-containing acid of phosphorus can be modified. In addition, it is speculated that the above-mentioned phosphorus atoms exist in the film formed on the surface of the positive electrode composite material. That is, it is speculated that the phosphorus atoms from the oxygen-containing acid of phosphorus exist in the film formed on the surface of the positive electrode composite material, so that the peak attributed to P2p exists at a position below 135eV in the X-ray photoelectron spectrum of the positive electrode composite material.

[0040] Examples of the positive electrode active material include lithium transition metal composite oxides and polyanion compounds. Examples of the lithium transition metal composite oxide include Li x MO y A composite oxide (Li having a layered α-NaFeO2 type crystal structure) represented by (M represents at least one transition metal) x CoO2、Li x NiO2、Li x MnO3、Li x Ni α Co (1-α) O2、Li x Ni α Co β Al (1-α-β) O2、Li x Ni α Mn β Co (1-α-β) O2、Li 1+x (Ni α Mn β Co (1-α-β) ) 1-x O2, etc., Li with spinel crystal structure x Mn2O4、Li x Ni α Mn (2-α) O4, etc.). In addition, examples of polyanionic compounds include Li w Me x (XO y ) z(Me represents at least one transition metal, X represents, for example, P, Si, B, V, etc.) represented by a polyanion compound (LiFePO4, LiMnPO4, LiNiPO4, LiCoPO4, Li3V2(PO4)3, Li2MnSiO4, Li2CoPO4F, etc.). The elements or polyanions in these compounds can be partially replaced by other elements or anion species. In the positive electrode composite layer, these compounds can be used alone or in combination of two or more.

[0041] The positive electrode active material preferably contains a non-aqueous electrolyte. The positive electrode potential of the storage element at the charge end voltage during normal use can be higher than 4.0 V (vs. Li / Li + ) positive electrode active material. As such a positive electrode active material, preferably a lithium transition metal composite oxide. This non-aqueous electrolyte storage element can be used even when the maximum potential reached by the positive electrode is higher than 4.0V (vs. Li / Li + ) can also suppress the increase in internal resistance after charge and discharge cycles. Therefore, by using the positive electrode working potential can reach 4.0V (vs. Li / Li + ) or more positive electrode active materials can be made into non-aqueous electrolyte storage elements with improved energy density and suppressed increase in internal resistance after charge and discharge cycles. Here, normal use refers to the situation where the non-aqueous electrolyte storage element is used using the recommended or specified charge and discharge conditions in the non-aqueous electrolyte storage element. Regarding charging conditions, when a charger for the non-aqueous electrolyte storage element is prepared, the situation where the non-aqueous electrolyte storage element is used using the charger is referred to as normal use.

[0042] As the lower limit of the proportion of the lithium transition metal composite oxide in the total positive electrode active material, preferably 50% by mass, more preferably 90% by mass, and further preferably 99% by mass. The positive electrode active material can be substantially composed of only the lithium transition metal composite oxide. By increasing the proportion of the lithium transition metal composite oxide in this way, the rise of the internal resistance after the charge and discharge cycle can be suppressed, and the energy density can be further improved.

[0043] The positive electrode active material preferably contains a non-aqueous electrolyte. The positive electrode working potential of the storage element in the charge end voltage during normal use can reach 4.4V (vs. Li / Li + ) or more positive electrode active material. The positive electrode working potential in the charge termination voltage during normal use can reach 4.4V (vs. Li / Li + ) above may refer to the positive electrode active material at 4.4V (vs.Li / Li +) or above. Examples of such positive electrode active materials include Li-ion having a layered α-NaFeO2 crystal structure. 1+x (Ni α Mn β Co (1-α-β) ) 1-x O2 (0<x<1, 0≤α<0.5, 0.5<β≤1, 0≤1-α-β<0.5), Li x Ni α Mn (2-α) An example of LiNi O4 0.5 Mn 1.5 O4, LiNiPO4, LiCoPO4, Li2CoPO4F, Li2MnSiO4, etc. as an example of a polyanion compound.

[0044] The content of the positive electrode active material in the positive electrode mixed material layer may be, for example, 80% by mass to 98% by mass, and preferably 90% by mass or more.

[0045] In the X-ray photoelectron spectrum of the positive electrode composite material, the upper limit of the position of the peak attributed to P2p is preferably 134 eV. On the other hand, the lower limit of the position of the peak may be 130 eV or 132 eV.

[0046] The conductive agent is not particularly limited as long as it is a conductive material that does not adversely affect the performance of the storage element. Examples of such conductive agents include natural or artificial graphite, furnace black, acetylene black, ketjen black and other carbon blacks, metals, conductive ceramics, etc., preferably acetylene black. Examples of the shape of the conductive agent include powder, fiber, etc.

[0047] Examples of the above-mentioned binder include thermoplastic resins such as fluororesins (polytetrafluoroethylene (PTFE), polyvinylidene fluoride (PVDF), etc.), polyethylene, polypropylene, polyimide, etc.; elastomers such as ethylene-propylene-diene rubber (EPDM), sulfonated EPDM, styrene-butadiene rubber (SBR), fluororubber, etc.; polysaccharide polymers, etc.

[0048] Examples of the thickener include polysaccharide polymers such as carboxymethyl cellulose (CMC) and methyl cellulose. When the thickener has a functional group that reacts with lithium, it is preferred that the functional group be inactivated in advance by methylation or the like.

[0049] The filler is not particularly limited as long as it does not adversely affect the performance of the energy storage device. Examples of the main component of the filler include polyolefins such as polypropylene and polyethylene, silica, alumina, zeolite, and glass.

[0050] (negative electrode)

[0051] The negative electrode comprises a negative electrode substrate and a negative electrode composite layer disposed on the negative electrode substrate directly or via an intermediate layer. The intermediate layer may have the same structure as the intermediate layer of the positive electrode.

[0052] The negative electrode substrate may be of the same configuration as the positive electrode substrate, and as a material, metals such as copper, nickel, stainless steel, nickel-plated steel, or alloys thereof may be used, preferably copper or a copper alloy. In other words, as the negative electrode substrate, copper foil is preferred. Examples of the copper foil include rolled copper foil, electrolytic copper foil, and the like.

[0053] The negative electrode composite layer is formed of a negative electrode composite containing a negative electrode active material. In addition, the negative electrode composite forming the negative electrode composite layer contains any components such as a conductive agent, a binder, a thickener, a filler, and a dispersant as required. The conductive agent, a binder, a thickener, a filler, a dispersant, and any components can use the same substances as those of the positive electrode composite layer.

[0054] As the above-mentioned negative electrode active material, generally, a material capable of absorbing and releasing lithium ions, etc. can be used. As specific negative electrode active materials, for example, metals or semimetals such as Si and Sn; metal oxides or semimetal oxides such as Si oxides and Sn oxides; polyphosphate compounds; carbon materials such as graphite and non-graphite carbon (graphitizable carbon or non-graphitizable carbon), etc. can be cited.

[0055] In addition, the negative electrode composite material (negative electrode composite material layer) may contain typical non-metallic elements such as B, N, P, F, Cl, Br, I, typical metal elements such as Li, Na, Mg, Al, K, Ca, Zn, Ga, Ge, and transition metal elements such as Sc, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Mo, Zr, Ta, Hf, Nb, and W.

[0056] (Isolator)

[0057] As the material of the above-mentioned separator, for example, fabric, non-woven fabric, porous resin film, etc. can be used. Among them, porous resin film is preferred from the viewpoint of strength, and non-woven fabric is preferred from the viewpoint of liquid retention of non-aqueous electrolyte. As the main component of the above-mentioned separator, for example, polyolefins such as polyethylene and polypropylene are preferred from the viewpoint of strength, and for example, polyimide, aramid, etc. are preferred from the viewpoint of anti-oxidative decomposition. In addition, these resins can also be composited.

[0058] It should be noted that an inorganic insulating layer may be provided between the separator and the electrode (usually the positive electrode). The inorganic insulating layer is a porous layer also referred to as a heat-resistant layer. In addition, a separator in which an inorganic insulating layer is formed on one or both sides of a porous resin film may be used. The inorganic insulating layer is usually composed of inorganic insulating particles and a binder, and may also contain other components. As inorganic insulating particles, Al2O3, SiO2, aluminosilicates, etc. are preferred.

[0059] (Non-aqueous electrolyte)

[0060] The non-aqueous electrolyte includes an imide salt and a non-aqueous solvent that dissolves the imide salt. It should be noted that the non-aqueous electrolyte is not limited to a liquid non-aqueous electrolyte. That is, the non-aqueous electrolyte also includes a solid or gel non-aqueous electrolyte.

[0061] (Imide salt)

[0062] Examples of the imide salt include lithium imide salts, sodium imide salts, potassium imide salts, and the like, and lithium imide salts are preferred.

[0063] Examples of the above-mentioned imide lithium salt include:

[0064] LiN(SO2F)2(lithium bis(fluorosulfonyl)imide: LiFSI), LiN(CF3SO2)2(lithium bis(trifluoromethanesulfonyl)imide: LiTFSI), LiN(C2F5SO2)2(lithium bis(pentafluoroethanesulfonyl)imide: LiBETI), LiN(C4F9SO2)2(lithium bis(nonafluorobutanesulfonyl)imide), CF3-SO2-N-SO2-N-SO2CF3Li, FSO2-N-SO2-C4F9Li, CF3-SO2-N-SO2-C4F9Li, CF3-SO2-N-SO2-CF2-SO2-N-SO2-CF3Li2, CF3-SO2-N-SO2-CF2-SO3Li2, CF3-SO2-N-SO2-CF2-SO2-C(-SO2CF3)2Li2 and other sulfonyl imide lithium salts;

[0065] Phosphinimide lithium salts such as LiN(POF2)2 (lithium bis(difluorophosphinyl)imide: LiDFPI) etc. Phosphinimide lithium salts may be used alone or in combination of two or more.

[0066] The imide lithium salt preferably has a fluorine atom, specifically, for example, preferably has a fluorosulfonyl group, a difluorophosphonyl group, a fluoroalkyl group, etc. Among the imide lithium salts, sulfonyl imide lithium salts are also preferred, LiFSI, LiTFSI and LiBETI are more preferred, and LiFSI is further preferred. These imide salts are when the working potential of the positive electrode reaches 4.0V (vs. Li / Li +) or more, which is more likely to cause aluminum oxidative corrosion during charge and discharge. Therefore, when such an imide salt is used, the following advantages of the present invention can be particularly effectively obtained: suppressing the working potential of the positive electrode from reaching 4.0V (vs. Li / Li + ) or more during charge and discharge, thereby suppressing the increase in internal resistance of the non-aqueous electrolyte storage element after charge and discharge cycles.

[0067] The lower limit of the content of the above-mentioned imide salt in the above-mentioned non-aqueous electrolyte is, for example, preferably 0.5 mol / kg, more preferably 0.8 mol / kg. By making the content of the imide salt above the above lower limit, the charge and discharge performance can be improved. On the one hand, the upper limit of the content is preferably 2 mol / kg, more preferably 1.4 mol / kg, further preferably 1.2 mol / kg, and further preferably 1.1 mol / kg. By making the content of the imide salt below the above upper limit, it is expected to suppress high viscosity and improve the high rate discharge performance of the non-aqueous electrolyte storage element at low temperature.

[0068] (Other electrolyte salts)

[0069] The above-mentioned non-aqueous electrolyte may further contain an electrolyte salt other than the above-mentioned imide salt, or may not contain it. As such an electrolyte salt, lithium salts, sodium salts, potassium salts, magnesium salts, onium salts, etc. other than imide salts can be cited. When containing an electrolyte salt other than an imide salt, as the upper limit of the content of the electrolyte salt other than the imide salt in the above-mentioned non-aqueous electrolyte, 1 mol / kg is sometimes preferred, 0.1 mol / kg is sometimes more preferred, and 0.01 mol / kg is sometimes further preferred. By making the content of the electrolyte salt other than the imide salt below the above-mentioned upper limit, the increase in internal resistance after the charge and discharge cycle can be effectively suppressed, and the capacity retention rate can be further improved. When the upper limit of the content of the electrolyte salt other than the imide salt in the above-mentioned non-aqueous electrolyte is 0.01 mol / kg, it is equivalent to that the above-mentioned non-aqueous electrolyte does not substantially contain an electrolyte salt other than the imide salt. The electrolyte salt other than the imide salt can be an electrolyte salt having a PF6 anion such as LiPF6.

[0070] It should be noted that when LiPF6 is used as other electrolyte salts, in the X-ray photoelectron spectrum of the positive electrode composite material, the peak belonging to P2p from LiPF6 exists at a position exceeding 135eV (usually in a range exceeding 135eV and below 138eV). Therefore, the peak belonging to P2p from LiPF6 can be distinguished from the peak belonging to P2p from the oxoacid of phosphorus based on the difference in peak position.

[0071] (Non-aqueous solvent)

[0072] As the above-mentioned nonaqueous solvent, the known nonaqueous solvent generally used as the nonaqueous solvent of the nonaqueous electrolyte for storage element can be used. As the above-mentioned nonaqueous solvent, carbonate (cyclic carbonate and chain carbonate), ester, ether, amide, sulfone, lactone, nitrile etc. can be mentioned. Wherein, preferably at least carbonate is used, more preferably cyclic carbonate and chain carbonate are used in combination. It should be noted that carbonate can be carbonate without substituent, or carbonate with substituent. As the substituent, hydroxyl, halogen atom etc. can be mentioned.

[0073] When using cyclic carbonate and linear carbonate, as the volume ratio of cyclic carbonate and linear carbonate (cyclic carbonate: linear carbonate), it is not particularly limited, for example, is preferably 5:95~50:50.In addition, as the lower limit of the shared content of cyclic carbonate in above-mentioned nonaqueous solvent, preferably 1 volume %, more preferably 5 volume %.On the other hand, as the upper limit of the content of cyclic carbonate, preferably 50 volume %, more preferably 40 volume %.As the lower limit of the shared content of linear carbonate in above-mentioned nonaqueous solvent, preferably 20 volume %, more preferably 50 volume %.On the other hand, as the upper limit of the content of linear carbonate, preferably 95 volume %, more preferably 90 volume %.

[0074] Examples of the cyclic carbonate include ethylene carbonate (EC), propylene carbonate (PC), butylene carbonate (BC), vinylene carbonate (VC), vinyl ethylene carbonate (VEC), ethylene chloride carbonate, fluoroethylene carbonate (FEC), difluoroethylene carbonate (DFEC), fluoromethylethylene carbonate, trifluoroethylethylene carbonate, styrene carbonate, catechol carbonate, 1-phenylvinylene carbonate, and 1,2-diphenylvinylene carbonate.

[0075] Examples of the chain carbonate include diethyl carbonate (DEC), dimethyl carbonate (DMC), ethyl methyl carbonate (EMC), diphenyl carbonate, methyl trifluoroethyl carbonate (MFEC), and bis(trifluoroethyl) carbonate (FDEC).

[0076] The non-aqueous solvent preferably contains a fluorinated carbonate. That is, the cyclic carbonate is preferably a fluorinated cyclic carbonate such as fluoroethylene carbonate, difluoroethylene carbonate, fluoromethylethylene carbonate, trifluoroethylethylene carbonate, etc. In addition, the chain carbonate is preferably a fluorinated chain carbonate such as methyl trifluoroethyl carbonate, bis (trifluoroethyl) carbonate, etc. The fluorinated carbonate is particularly capable of suppressing the reaction at 4.0 V (vs. Li / Li + ) or above, thereby suppressing the increase in internal resistance after charge and discharge cycles, increasing capacity retention, and further improving charge and discharge cycle performance.

[0077] In addition, among the above-mentioned non-aqueous solvents, fluorinated solvents other than fluorinated carbonates may be used. Examples of such fluorinated solvents include fluorinated ethers such as 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether and 1,1,2,2-tetrafluoroethyl-2,2,2-trifluoroethyl ether (TFEE).

[0078] The lower limit of the total content of the fluorinated solvent containing the fluorinated carbonate in the non-aqueous solvent is preferably 20% by volume, more preferably 50% by volume, further preferably 80% by volume, further preferably 90% by volume, and further preferably 99% by volume. By making the total content of the fluorinated solvent containing the fluorinated carbonate above the lower limit, the 4.0V (vs. Li / Li + ) or above, can further improve the capacity retention rate.

[0079] Other additives may be added to the non-aqueous electrolyte. The upper limit of the content of the electrolyte salt containing the imide salt and the components other than the non-aqueous solvent in the non-aqueous electrolyte is preferably 5% by mass, more preferably 1% by mass, and further preferably 0.1% by mass.

[0080] The non-aqueous electrolyte storage element has a maximum potential of 4.0 V (vs. Li / Li + ) or more charge and discharge cycles, the internal resistance increase is suppressed, and the capacity retention rate is also high, so it can be 4.0V (vs. Li / Li + ) or more. The lower limit of the maximum potential of the positive electrode of the non-aqueous electrolyte storage element can be, for example, 4.0 V (vs. Li / Li + ) or 4.2V(vs.Li / Li + ), preferably 4.4V (vs. Li / Li + ), more preferably 4.5V (vs.Li / Li + ), more preferably 4.6V (vs. Li / Li + ), and further preferably 4.7V (vs. Li / Li + ). By making the maximum potential of the positive electrode higher, high energy density can be achieved. It should be noted that the upper limit of the maximum potential of the positive electrode is, for example, 5.4V (vs. Li / Li + ), or 5.0V (vs.Li / Li + ).

[0081] The maximum potential reached by the positive electrode is preferably the positive electrode potential at the charge termination voltage of the non-aqueous electrolyte storage element in normal use. Generally, when the positive electrode is frequently brought to a high potential due to repeated charge and discharge, an increase in internal resistance and a decrease in capacity are likely to occur. Therefore, when the maximum potential reached by the positive electrode is frequently brought to, for example, 4.4V (vs. Li / Li + ) or more, the effect of suppressing the increase in internal resistance of the non-aqueous electrolyte storage element after charge and discharge cycles and the effect of improving the capacity retention rate can be more clearly reflected.

[0082] <Method for producing non-aqueous electrolyte storage element>

[0083] The nonaqueous electrolyte storage element is preferably manufactured by the following method. That is, the method for manufacturing a nonaqueous electrolyte storage element according to one embodiment of the present invention uses a positive electrode having a positive electrode composite material prepared using a positive electrode composite material paste containing an oxoacid containing phosphorus and a nonaqueous electrolyte containing an imide salt.

[0084] For example, in one example of the method for manufacturing the nonaqueous electrolyte storage element, the following steps are included:

[0085] A positive electrode is produced using a positive electrode composite paste containing an oxygen-containing acid of phosphorus (positive electrode production step), and

[0086] A non-aqueous electrolyte containing an imide salt is injected into the container (non-aqueous electrolyte injection step).

[0087] (Positive electrode manufacturing process)

[0088] The positive electrode composite material paste usually contains a positive electrode active material and a binder in addition to the oxyacid of phosphorus, and contains other components as needed. The positive electrode composite material paste can be obtained by mixing these components. The positive electrode composite material paste is applied to the surface of the positive electrode substrate and dried to obtain a positive electrode in which the peak belonging to P2p in the X-ray photoelectron spectrum of the positive electrode composite material is present at a position below 135eV.

[0089] The above-mentioned phosphorus oxygen-containing acid refers to a compound having a structure in which a hydroxyl group (-OH) and an oxygen group (=O) are bonded to a phosphorus atom. Examples of the above-mentioned phosphorus oxygen-containing acid include phosphoric acid (H3PO4), phosphonic acid (H3PO3), phosphinic acid (H3PO2), pyrophosphoric acid (H4P2O7), and polyphosphoric acid. Among them, phosphoric acid and phosphonic acid are preferred, and phosphonic acid is more preferred. By using the phosphorus oxygen-containing acid, a film containing phosphorus atoms is formed on the positive electrode, and a positive electrode is obtained in which the peak attributed to P2p in the X-ray photoelectron spectrum of the positive electrode composite material is present at a position below 135eV. If a metal salt of a phosphorus oxygen-containing acid (lithium salt, sodium salt, potassium salt, magnesium salt, calcium salt, etc.) or an ester of a phosphorus oxygen-containing acid (phosphate ester, phosphonic acid ester, etc.) is used instead of the phosphorus oxygen-containing acid, a positive electrode in which the peak attributed to P2p in the X-ray photoelectron spectrum of the positive electrode composite material is present at a position below 135eV cannot be obtained, and the effect of the present invention cannot be achieved.

[0090] As the lower limit of the content (addition amount) of the oxyacid of phosphorus in the above-mentioned positive electrode composite paste, relative to 100 parts by mass of the positive electrode active material, preferably 0.05 parts by mass, more preferably 0.1 parts by mass, and further preferably 0.3 parts by mass. On the other hand, as the upper limit of the content, preferably 5 parts by mass, more preferably 3 parts by mass, and further preferably 2 parts by mass. By making the content of the oxyacid of phosphorus in the above range, the increase of the internal resistance after the charge and discharge cycle can be more effectively suppressed, and the capacity retention rate can be further improved.

[0091] An organic solvent is generally used as a dispersion medium in the positive electrode material paste, and examples of the organic solvent include polar solvents such as N-methyl-2-pyrrolidone (NMP), acetone, and ethanol, and non-polar solvents such as xylene, toluene, and cyclohexane.

[0092] The method for applying the positive electrode material paste is not particularly limited, and the positive electrode material paste may be applied by a known method such as a roll coating method, a screen coating method, or a spin coating method.

[0093] (Non-aqueous electrolyte injection step)

[0094] The nonaqueous electrolyte injection step can be performed by a known method. That is, a nonaqueous electrolyte having a desired composition can be prepared and the prepared nonaqueous electrolyte can be injected into the container.

[0095] In addition to the above-mentioned positive electrode production process and non-aqueous electrolyte injection process, the manufacturing method may also have the following process, etc. That is, the manufacturing method may, for example, have the following process: the process of making a negative electrode, the process of stacking or winding the positive electrode and the negative electrode through a separator to form an alternately overlapping electrode body, and the process of accommodating the positive electrode and the negative electrode (electrode body) in a container. Usually, after the electrode body is accommodated in a container, the non-aqueous electrolyte is injected into the container, but the order may also be reversed. After these processes, a non-aqueous electrolyte storage element can be obtained by sealing the injection port.

[0096] <Other embodiments>

[0097] The present invention is not limited to the above-mentioned embodiment. In addition to the above-mentioned manner, it can also be implemented in a manner that various changes and improvements are applied. For example, in the above-mentioned positive electrode or negative electrode, an intermediate layer may not be provided. In addition, in the positive electrode of the non-aqueous electrolyte storage element, the positive electrode composite material may not form a clear layer. For example, the above-mentioned positive electrode may also be a structure in which a positive electrode composite material is carried on a mesh-like positive electrode substrate.

[0098] In addition, in the above embodiment, the nonaqueous electrolyte storage element is described as a nonaqueous electrolyte secondary battery, but other nonaqueous electrolyte storage elements may be used. Other nonaqueous electrolyte storage elements include capacitors (electric double layer capacitors, lithium ion capacitors), etc.

[0099] Figure 1 1 is a schematic diagram of a rectangular non-aqueous electrolyte storage element 1 as one embodiment of the non-aqueous electrolyte storage element of the present invention. Figure 1 This is a diagram of the interior of the perspective container. Figure 1 The non-aqueous electrolyte storage element 1 shown has an electrode body 2 stored in a container 3. The electrode body 2 is formed by winding a positive electrode having a positive electrode composite and a negative electrode having a negative electrode composite with a separator. The positive electrode is electrically connected to a positive electrode terminal 4 via a positive electrode lead 4', and the negative electrode is electrically connected to a negative electrode terminal 5 via a negative electrode lead 5'. In addition, a non-aqueous electrolyte is injected into the container 3.

[0100] The structure of the non-aqueous electrolyte storage element of the present invention is not particularly limited. As an example, a cylindrical battery, a square battery (rectangular battery), a flat battery, etc. can be cited. The present invention can also be implemented in the form of a storage device having a plurality of the above-mentioned non-aqueous electrolyte storage elements. One embodiment of the storage device is shown in Figure 2 . Figure 2In the embodiment, the power storage device 30 includes a plurality of power storage cells 20. Each power storage cell 20 includes a plurality of non-aqueous electrolyte storage elements 1. The power storage device 30 can be mounted as a power source for vehicles such as electric vehicles (EV), hybrid electric vehicles (HEV), and plug-in hybrid electric vehicles (PHEV).

[0101] Example

[0102] Hereinafter, the present invention will be described in more detail with reference to Examples, but the present invention is not limited to the following Examples.

[0103] (Production of positive electrode P1)

[0104] As the positive electrode active material, a Li 1+α Me 1-α A lithium transition metal composite oxide represented by O2 (Me is a transition metal containing Mn, 0.1<α<0.2, and the molar ratio of Mn to Me Mn / Me is 0.5<Mn / Me). Using N-methylpyrrolidone (NMP) as a dispersion medium, the above-mentioned positive electrode active material, acetylene black (AB) as a conductive agent, polyvinylidene fluoride (PVDF) as a binder, and phosphonic acid (H3PO3) are mixed in a mass ratio of 94-X:4.5:1.5:X in terms of solid content to obtain a positive electrode composite paste. It should be noted that X (mixing ratio of phosphonic acid) is 0.2 or 1, and no difference is observed when X is 0.2 and 1 in any evaluation described below. The positive electrode composite paste is applied to one side of an aluminum foil as a positive electrode substrate, and heated and dried at 100°C to form a positive electrode composite layer on the positive electrode substrate. In addition, the positive electrode material paste was similarly applied to the opposite surface of the aluminum foil and dried by heating at 100° C. The positive electrode material layer formed on the opposite surface was peeled off after drying, thereby obtaining a positive electrode P1.

[0105] (Production of positive electrode R1)

[0106] Positive electrode R1 was obtained in the same manner as in the above-mentioned “Production of positive electrode P1” except that phosphonic acid was not mixed into the positive electrode mixed material paste.

[0107] (Production of positive electrode P2)

[0108] As the positive electrode active material, LiNi 1 / 3 Co 1 / 3 Mn 1 / 3A lithium transition metal composite oxide represented by O2. Using N-methylpyrrolidone (NMP) as a dispersion medium, the above-mentioned positive electrode active material, acetylene black (AB) as a conductive agent, polyvinylidene fluoride (PVDF) as a binder, and phosphonic acid (H3PO3) are mixed in a mass ratio of 95.5:2:2:0.5 calculated as solid content to obtain a positive electrode composite paste. The positive electrode composite paste is applied to a single side of an aluminum foil as a positive electrode substrate, and heated and dried at 100°C to form a positive electrode composite layer on the positive electrode substrate. In addition, the positive electrode composite paste is also applied to the surface on the opposite side of the aluminum foil, and heated and dried at 100°C. The positive electrode composite layer formed on the surface on the opposite side is peeled off after drying. Thus, the positive electrode P2 is obtained.

[0109] (Production of positive electrode R2)

[0110] A positive electrode R2 was obtained in the same manner as in the above-mentioned “production of positive electrode P2” except that phosphonic acid was not mixed into the positive electrode material paste.

[0111] (Production of positive electrode P3)

[0112] The same positive electrode composite material paste as that used to make the positive electrode P2 was applied to one side of an aluminum foil as a positive electrode substrate, and heated and dried at 100°C, thereby forming a positive electrode composite material layer on the positive electrode substrate. In addition, the positive electrode composite material paste was also applied to the opposite side of the aluminum foil, and heated and dried at 100°C. The positive electrode composite material layer formed on the opposite side was peeled off after drying. Thus, the positive electrode P3 was obtained.

[0113] (Production of positive electrode R3)

[0114] Positive electrode R3 was obtained in the same manner as in the above-mentioned “Production of positive electrode P3” except that phosphonic acid was not mixed into the positive electrode composite paste.

[0115] (Production of negative electrode)

[0116] A negative electrode using graphite as a negative electrode active material was produced.

[0117] [Example 1]

[0118] (Preparation of non-aqueous electrolyte)

[0119] Lithium bis(fluorosulfonyl)imide (LiFSI) as an electrolyte salt was dissolved at a concentration of 1.0 mol / kg in a mixed solvent of fluoroethylene carbonate (FEC) and methyl trifluoroethyl carbonate (MFEC) at a volume ratio of 3:7 to prepare a nonaqueous electrolyte.

[0120] (Fabrication of non-aqueous electrolyte storage element)

[0121] The positive electrode P1 and the negative electrode are stacked via a separator made of a polyolefin microporous film to produce an electrode body. The electrode body is housed in a container made of a metal-resin composite film, the nonaqueous electrolyte is injected into the container, and then sealed by hot melting to obtain the nonaqueous electrolyte storage element (laminated nonaqueous electrolyte secondary battery) of Example 1.

[0122] [Examples 2 to 6, Comparative Examples 1 to 6, Reference Examples 1 to 2]

[0123] Each nonaqueous electrolyte storage element of Examples 2 to 6, Comparative Examples 1 to 6, and Reference Examples 1 to 2 was obtained in the same manner as in Example 1 except that the types of the positive electrode and electrolyte salt, and the types and mixing volume ratios of the solvent were as shown in Tables 1 to 3.

[0124] In addition, the solvents in the table show the following compounds.

[0125] FEC: Fluoroethylene carbonate

[0126] MFEC: Methyl trifluoroethyl carbonate

[0127] TFEE: 1,1,2,2-tetrafluoroethyl-2,2,2-trifluoroethyl ether

[0128] EMC: Ethyl Methyl Carbonate

[0129] EC: Ethylene carbonate

[0130] [Evaluation 1] Charge and discharge voltage range 4.6~2.0V

[0131] (Initial charge and discharge)

[0132] The non-aqueous electrolyte storage elements of Examples 1 to 4, Comparative Examples 1 to 4, and Reference Examples 1 to 2 were initially charged and discharged under the following conditions. After charging to 4.6 V at a constant current of 0.1 C at 25°C, the cells were charged at a constant voltage of 4.6 V. The charging was terminated when the charging current reached 0.05 C. After a 10-minute rest period after charging, the cells were discharged to 2.0 V at a constant current of 0.1 C at 25°C.

[0133] (X-ray photoelectron spectroscopy)

[0134] Each non-aqueous electrolyte storage element in a fully discharged state after the initial charge and discharge is disassembled in an argon atmosphere with a dew point below -60°C, and the positive electrode is taken out. After the positive electrode is cleaned with dimethyl carbonate, it is dried under reduced pressure at room temperature. The obtained positive electrode is sealed in a transition chamber in an argon atmosphere, introduced into the sample chamber of the X-ray photoelectron spectroscopy measuring device, and the X-ray photoelectron spectroscopy measurement of the positive electrode composite surface of the positive electrode is carried out under the above conditions. From the obtained energy spectrum, the peak position attributable to P2p is obtained using the above method. In the positive electrode composite (P1) of Examples 1 to 4 and Reference Example 1 using phosphonic acid, the peak attributable to P2p exists between 133 and 134 eV. In the positive electrode composite (R1) of Comparative Examples 1 to 4 and Reference Example 2 without using phosphonic acid, the peak attributable to P2p cannot be seen in the range below 135 eV. It should be noted that in the positive electrode composites of Reference Examples 1 and 2 using LiPF 6 as the electrolyte salt, a peak attributable to P2p derived from LiPF 6 was observed at 136 eV.

[0135] (Charge and discharge cycle test)

[0136] After the initial charge and discharge, each non-aqueous electrolyte storage element was stored in a thermostatic chamber at 45°C for 2 hours, and then charged to 4.6V at a constant current of 1.0C, and then charged at a constant voltage of 4.6V. The charging end condition was when the charging current reached 0.05C. The positive electrode potential (= the maximum potential reached by the positive electrode) at the end of charging was 4.7V (vs. Li / Li + ). After charging, set a rest period of 10 minutes, and then discharge to 2.0V at a constant current of 1.0C. Set a rest period of 10 minutes after discharging. These charging, discharging and resting steps are regarded as one cycle, and this cycle is repeated 50 times. Charging, discharging and resting are all carried out in a constant temperature chamber at 45℃.

[0137] (Internal resistance)

[0138] The internal resistance (ACR) of each nonaqueous electrolyte storage element before and after the charge-discharge cycle test was measured by an alternating current (1 kHz) method. The ratio of the internal resistance (ACR) after the charge-discharge cycle test to the internal resistance (ACR) before the charge-discharge cycle test is shown in Table 1 as the ACR ratio.

[0139] (Capacity retention rate)

[0140] For each nonaqueous electrolyte energy storage device, the discharge capacity at the 50th cycle relative to the discharge capacity at the 1st cycle in the above-mentioned charge and discharge cycle test is shown in Table 1 as the capacity retention rate (%).

[0141] [Table 1]

[0142]

[0143] [Evaluation 2] Charge and discharge voltage range 4.35~2.75V

[0144] The nonaqueous electrolyte storage devices of Example 5 and Comparative Example 5 were set to a charge end voltage of 4.35 V (maximum potential of the positive electrode: 4.45 V (vs. Li / Li + )), the discharge termination voltage was set to 2.75V. Otherwise, the initial charge and discharge and charge and discharge cycle tests were carried out in the same manner as in the above-mentioned "Evaluation 1". After the initial charge and discharge, the X-ray photoelectron spectroscopy of the surface of the positive electrode composite was carried out in the same manner as in the above-mentioned "Evaluation 1". In the positive electrode composite (P2) of Example 5 using phosphonic acid, the peak attributed to P2p exists between 133 and 134 eV. In the positive electrode composite (R2) of Comparative Example 5 in which phosphonic acid is not used, the peak attributed to P2p cannot be seen in the range below 135 eV. In addition, the internal resistance and capacity retention rate were measured in the same manner as in the above-mentioned "Evaluation 1". The measurement results are shown in Table 2.

[0145] [Table 2]

[0146]

[0147] [Evaluation 3] Charge and discharge voltage range 4.2~2.75V

[0148] The nonaqueous electrolyte storage devices of Example 6 and Comparative Example 6 were set to a charge end voltage of 4.2 V (maximum potential of the positive electrode: 4.3 V (vs. Li / Li + )), the discharge termination voltage was set to 2.75V. Otherwise, the initial charge and discharge and charge and discharge cycle tests were carried out in the same manner as in the above-mentioned "Evaluation 1". After the initial charge and discharge, the X-ray photoelectron spectroscopy of the surface of the positive electrode composite was carried out in the same manner as in the above-mentioned "Evaluation 1". In the positive electrode composite (P3) of Example 6 using phosphonic acid, the peak attributed to P2p exists between 133 and 134 eV. In the positive electrode composite (R3) of Comparative Example 6 in which phosphonic acid is not used, the peak attributed to P2p cannot be seen in the range below 135 eV. In addition, the internal resistance and capacity retention rate were measured in the same manner as in the above-mentioned "Evaluation 1". The measurement results are shown in Table 3.

[0149] [Table 3]

[0150]

[0151] [Investigation]

[0152] (Internal resistance)

[0153] According to the comparison between Example 1 and Comparative Example 1 in Table 1 above, it can be seen that in the non-aqueous electrolyte storage element in which the non-aqueous electrolyte contains an imide salt as the electrolyte salt, by using a positive electrode P1 in which the peak belonging to P2p in the X-ray photoelectron spectrum of the positive electrode composite is present at a position below 135 eV, the ACR is relatively small, and the increase in internal resistance after the charge and discharge cycle is suppressed. The same trend can also be confirmed by the comparison between Example 4 and Comparative Example 4 in Table 1, the comparison between Example 5 and Comparative Example 5 in Table 2, and the comparison between Example 6 and Comparative Example 6 in Table 3. It should be noted that Example 1 and the like are not examples in which the internal resistance becomes smaller after the charge and discharge cycle compared to before the charge and discharge cycle, but examples in which the increase in internal resistance accompanying the charge and discharge cycle is suppressed. Among them, it can be seen that: like Examples 1 and 4, the maximum potential reached by the positive electrode reaches 4.6V (vs. Li / Li + ) or more charge-discharge cycles, by using a positive electrode P1 in which the peak attributed to P2p in the X-ray photoelectron spectrum of the positive electrode composite is present at a position below 135 eV, the ACR ratio is reduced, and the effect of suppressing the increase of the internal resistance after the charge-discharge cycle is significantly exerted (see Table 1). This is believed to be because the working potential of the positive electrode when using an imide salt as the electrolyte salt reaches 4.0 V (vs. Li / Li + ) and above during charge and discharge, and is more obviously produced when the maximum potential reached by the positive electrode is higher. However, the effect of the film derived from the oxygen-containing acid of phosphorus formed on the above-mentioned positive electrode composite material is exerted regardless of the maximum potential reached by the positive electrode.

[0154] On the other hand, according to the comparison between Reference Example 1 and Reference Example 2 in Table 1 above, when LiPF6 is used as the electrolyte salt, even if the positive electrode P1 in which the peak attributed to P2p in the X-ray photoelectron spectrum of the positive electrode composite is present at a position below 135 eV is used, the increase in internal resistance after the charge and discharge cycle cannot be suppressed. On the contrary, the ACR ratio (the rate of increase in internal resistance after the charge and discharge cycle) becomes larger than that of the case where the previous positive electrode R1 is used. That is, it can be said that the effect of suppressing the increase in internal resistance after the charge and discharge cycle is a specific effect that is first produced when the imide salt as the electrolyte salt is combined with the positive electrodes P1 to P3 in which the peak attributed to P2p in the X-ray photoelectron spectrum of the positive electrode composite is present at a position below 135 eV.

[0155] In addition, according to the comparison between Comparative Example 1 and Reference Example 2, it can be seen that when the conventional positive electrode R1 is used, if the electrolyte salt is changed from LiPF6 (Reference Example 2) to an imide salt (Comparative Example 1), the ACR ratio (the rate of increase of the internal resistance after the charge and discharge cycle) increases significantly. This result is consistent with the fact that the working potential of the imide salt at the positive electrode reaches 4.0V (vs. Li / Li +) or more is consistent with the previous view that oxidative corrosion of aluminum is easily generated during charge and discharge. Thus, based on the previous view, it is believed that when the electrolyte salt is replaced from LiPF6 to an imide salt, oxidative corrosion of aluminum is carried out, so the rate of increase of the internal resistance after the charge and discharge cycle becomes much higher. However, according to the comparison between Example 1 and Reference Example 1, it can be seen that: when the positive electrode P1 is a positive electrode in which the peak attributed to P2p in the X-ray photoelectron spectrum of the positive electrode composite is present at a position below 135eV, if the electrolyte salt is replaced from LiPF6 (Reference Example 1) to an imide salt (Example 1), the result is that the ACR ratio becomes smaller, and the increase of the internal resistance after the charge and discharge cycle is suppressed. Therefore, it can be said that: in the case of using a positive electrode in which the peak attributed to P2p in the X-ray photoelectron spectrum of the positive electrode composite is present at a position below 135eV, the effect of suppressing the increase of the internal resistance after the charge and discharge cycle by using an imide salt that is prone to oxidative corrosion of aluminum as the electrolyte salt is a specific effect that is completely unpredictable based on previous views.

[0156] (Capacity retention rate)

[0157] When focusing on the capacity retention rate after the charge and discharge cycle, it can be seen from the comparison of Example 1 and Reference Example 1 in Table 1 above that: in the case of the positive electrode P1 in which the peak belonging to P2p in the X-ray photoelectron spectrum of the positive electrode composite is present at a position below 135eV, the capacity retention rate after the charge and discharge cycle is improved by using an imide salt as an electrolyte salt. On the other hand, as shown in the comparison between Comparative Example 1 and Reference Example 2, when the previous positive electrode R1 is used, according to previous insights, when the electrolyte salt is replaced from LiPF6 (Reference Example 1) to an imide salt (Example 1), the capacity retention rate after the charge and discharge cycle is reduced. That is, it can be said that: in the case of the positive electrode P1 in which the peak belonging to P2p in the X-ray photoelectron spectrum of the positive electrode composite is present at a position below 135eV, the effect of improving the capacity retention rate after the charge and discharge cycle by using an imide salt that is prone to oxidative corrosion of aluminum as an electrolyte salt is a specific effect that cannot be predicted based on previous insights.

[0158] In addition, according to other Examples 2 to 6, it can be seen that in a non-aqueous electrolyte storage element using an imide salt, by using positive electrodes P1 to P3 in which the peak attributed to P2p in the X-ray photoelectron spectrum of the positive electrode composite is present at a position below 135 eV, the capacity retention rate after charge and discharge cycles is improved. It is believed that this is because the oxidative corrosion of aluminum caused by the imide salt is suppressed by using the positive electrodes P1 to P3 without relying on the solvent composition. It can be said that this effect is first produced when the imide salt as an electrolyte salt is combined with the positive electrodes P1 to P3 in which the peak attributed to P2p in the X-ray photoelectron spectrum of the positive electrode composite is present at a position below 135 eV.

[0159] Industrial Applicability

[0160] The present invention can be applied to non-aqueous electrolyte storage elements used as power sources for electronic devices such as personal computers and communication terminals, and automobiles.

[0161] Explanation of symbols

[0162] 1 Non-aqueous electrolyte storage element

[0163] 2 Electrode body

[0164] 3 Container

[0165] 4 Positive terminal

[0166] 4' positive lead

[0167] 5 Negative terminal

[0168] 5' negative lead

[0169] 20 Storage unit

[0170] 30 Power storage device

Claims

1. A non-aqueous electrolyte storage element comprising: positive electrode, and A non-aqueous electrolyte containing an imide salt; The positive electrode comprises a positive electrode substrate and a positive electrode composite material layer. The positive electrode substrate contains aluminum or an aluminum alloy. The positive electrode composite material contains positive electrode active material and phosphorus atoms. In the X-ray photoelectron spectrum of the positive electrode composite material, the peak attributed to P2p exists at a position below 135 eV. The positive electrode active material contains a non-aqueous electrolyte storage element. The positive electrode potential at the charge termination voltage during normal use can be higher than 4.0 V (vs. Li / Li + ) of the positive electrode active material, The content of the imide salt in the non-aqueous electrolyte is 0.5 mol / kg to 1.4 mol / kg.

2. The nonaqueous electrolyte storage element according to claim 1, wherein In the X-ray photoelectron spectrum of the positive electrode composite material, a peak attributed to P2p exists at a position below 134 eV.

3. The nonaqueous electrolyte storage element according to claim 1, wherein The content of the imide salt in the non-aqueous electrolyte is 0.8 mol / kg or more.

4. The nonaqueous electrolyte storage element according to claim 1, wherein The content of the imide salt in the non-aqueous electrolyte is 1.2 mol / kg or less.

5. The nonaqueous electrolyte storage element according to claim 1, wherein The content of the imide salt in the non-aqueous electrolyte is 1.1 mol / kg or less.

6. The nonaqueous electrolyte storage element according to any one of claims 1 to 5, wherein The imide salt includes an imide lithium salt.

7. The nonaqueous electrolyte storage element according to claim 6, wherein The imide lithium salt includes any one of a fluorosulfonyl group, a difluorophosphonyl group, and a fluoroalkyl group.

8. The nonaqueous electrolyte storage element according to claim 6, wherein The imide lithium salt includes a sulfonyl imide lithium salt.

9. The nonaqueous electrolyte storage element according to any one of claims 1 to 5, wherein The lithium imide salt comprises lithium bis(fluorosulfonyl)imide.

10. The nonaqueous electrolyte storage element according to any one of claims 1 to 5, wherein The non-aqueous electrolyte does not substantially contain an electrolyte salt having a PF6 anion.

11. The nonaqueous electrolyte storage element according to any one of claims 1 to 5, wherein The nonaqueous electrolyte includes a fluorinated carbonate.

12. The nonaqueous electrolyte storage element according to any one of claims 1 to 5, wherein The maximum potential of the positive electrode is 4.4V (vs. Li / Li + )above.

13. The nonaqueous electrolyte storage element according to any one of claims 1 to 5, wherein The maximum potential of the positive electrode is 4.5V (vs. Li / Li + )above.

14. The nonaqueous electrolyte storage element according to any one of claims 1 to 5, wherein The maximum potential of the positive electrode is 4.6V (vs. Li / Li + )above.

15. A method for producing a nonaqueous electrolyte storage element according to any one of claims 1 to 14, using a positive electrode and a nonaqueous electrolyte containing an imide salt, The positive electrode has a positive electrode composite material produced using a positive electrode composite material paste, and the positive electrode composite material paste contains an oxygen-containing acid of phosphorus.

16. The method for producing a non-aqueous electrolyte storage element according to claim 15, wherein: The phosphorus oxyacid comprises phosphoric acid or phosphonic acid.

Citation Information

Patent Citations

  • Electrode for lithium ion battery

    JP2011070773A

  • Lithium ion secondary battery

    JP2015079636A

  • Nonaqueous electrolyte electricity storage element and method for producing same

    WO2017099201A1